2023
DOI: 10.1093/procel/pwad040
|View full text |Cite
|
Sign up to set email alerts
|

Two antibodies show broad, synergistic neutralization against SARS-CoV-2 variants by inducing conformational change within the RBD

Abstract: Continual evolution of the SARS-CoV-2 virus has allowed for its gradual evasion of neutralizing antibodies (nAbs) produced in response to natural infection or vaccination. The rapid nature of these changes has incited a need for the development of superior broad nAbs and/or the rational design of an antibody cocktail that can protect against the mutated virus strain. Here, we report two ACE2 competing nAbs—8H12 and 3E2—with synergistic neutralization but evaded by some Omicron subvariants. Cryo-EM reveals the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
1
0
0
Order By: Relevance
“…Most of the bsAb combinations produced in this study had retained or even increased binding strength to S proteins of different sarbecoviruses. Others have reported synergistic neutralization of SARS-CoV-2 variants combining broad class 4 mAbs with more specific class 1 mAbs 59 , and similarly to this study, class 3 and 4 mAbs 48,60 . Of note, in a previous study 48 , a mix of class 3 CV38-142 and class 4 COVA1-16 showed modest synergistic effects.…”
Section: Discussionsupporting
confidence: 85%
“…Most of the bsAb combinations produced in this study had retained or even increased binding strength to S proteins of different sarbecoviruses. Others have reported synergistic neutralization of SARS-CoV-2 variants combining broad class 4 mAbs with more specific class 1 mAbs 59 , and similarly to this study, class 3 and 4 mAbs 48,60 . Of note, in a previous study 48 , a mix of class 3 CV38-142 and class 4 COVA1-16 showed modest synergistic effects.…”
Section: Discussionsupporting
confidence: 85%